A cross-linking strategy provides a new generation of biodegradable and biocompatible cyanoacrylate medical adhesives. Issue 23 (23rd May 2016) - Xu, Liang; Zhang, Tao; Dong, Huajin; Cai, Dazheng; Han, Han; Meng, Qingbin; Tang, Yongjia; Meng, Qingguo; Gong, Zehui; Zhang, Tianhong; Zhang, Zhenqing; Yan, Husheng; et al.
Abstract : A general strategy provides a new generation of biodegradable and biocompatible cyanoacrylate medical adhesives. Abstract : Addition polymerization usually results in polymers with long carbon–carbon main chains. Cyanoacrylate (CA) is arguably an important example of such polymerization and has gained widespread acceptance as an all-purpose adhesive. However, CA-based medical adhesives have never been approved by the U.S. Federal Drug Administration for use below the skin, mainly due to the low biodegradability and biocompatibility of their solid glue after polymerization. In this research, a cross-linking strategy involving the combination of alkyl-CA and the cross-linking agent poly(ethylene glycol)–di(cyanoacrylate) (CA–PEG–CA) to form a copolymeric network was used to synthesize a new generation of biodegradable CA medical adhesives. The degradability could be modulated by adjusting the ratio of CA–PEG–CA to alkyl-CA and the length of PEG. An optimal composite adhesive, LKJ11, was shown to have excellent biodegradability, adhesive capability, and biocompatibility. Importantly, the molecular weight of polycyanoacrylate chains in the polymerized LKJ11 was greatly reduced compared to those polymerized from pure butyl-CA. Thus, the degradation product could be readily extracted. The results showed that LKJ11 represents a new generation of CA-based biodegradable medical adhesives. This advance also provides a general strategy to facilitate the conversion of other polymers with long carbon–carbon main chains to a biodegradable form, thereby expanding the novel applications available for traditional polymeric materials.